Negotiating sacred space: a typological study on tomb mosques in the Malay world - Md. Sharif, Harlina (IIUM Press, 2020)
The objective of the study is to analyse the distinguishing features of tomb mosques in the Malay world. Based on an initial investigation on the morphology of the Malay World’s mosques’ designs and typology, a peculiar type of mosques with vast cemetery areas was identified. Although the emergence of mausoleums in Islam is known to have begun as early as the 9th century in Samarra, Iraq; however the existence of funerary architecture in the Malay World has never been studied in detail. From a list of forty mosques selected from various important port cities of the region, spanning from the 15th to the 20th century, ten mosques with necropolis area have been shortlisted for further studies. Four of these mosques are located in Java, Indonesia; while the rest are from the Malay Peninsula. By adopting analytical and generative typological methods, the design parameters of the mosques were extracted. The outcome of the analyses demonstrated the distinguishing qualities of the tomb mosques in the Malay World and highlighted as to whether their existence is in compliance with the spirit and text of the Islamic revelation.